Chemometric Assessment of Orashi River after Confluence with Oguta Lake - Enyoh Christian Ebere; Verla Andrew Wirnkor; Verla Evelyn Ngozi; Peter Ndu Okeke; Shirish S Pingale (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2019)
This study was carried out to evaluate the surficial water and sediment of Orashi River after confluence with Oguta. A total of 50 sub-samples were collected for the two media and were homogenized to form 10 composite samples (5 each). Water and sediment samples were analyzed for heavy metals concentrations and physico-chemical parameters. Data obtained was interpreted using ten chemometric models and standards of the Federal Ministry of Environment as touchstone values. Approximately 100 % of water samples were contaminated as opposed to 40 % of sediment samples. Both water and sediments showed that Cd  as the highest contaminant with contamination factors of 38 and 1.52 respectively. Water revealed pollution load index higher than sediment probably due to its dissolution ability to metals. Geo accumulation index was observed to have highest value for Cd (45) at point A while Fe (> 4) at all points and same time the highest negative value. All points exhibited very high ecological risk (RI; 1112.7–1473.9) for water while sediments at those points showed low (RI < 150). The water quality index (WQI) ranged from 1633.33–2275.57 with a minimum deviation of 1910 % from WQI (100) adjudged to be unsuitable for consumption. The exchangeable sodium percentage (ESP) for all sampling sites ranged from 0.17-0.25 % suggesting good water for irrigation purposes. There was low sodium absorption ratio (SAR) and cation ratio of structural stability (CROSS) for the river water showing that it is good for irrigation. The sediment quality index was all less than 1 indicating no pollution of sediment. Transfer factors followed the order As>Cd>Ag>Cr>Fe>Cu>Mn>Co>Ni. In conclusion, the water was polluted but good for irrigation use. However, continuous use could lead to health problems due to bioaccumulation of metals while sediments were generally not polluted and of good quality